Two dimensional materials beyond MoS2: Noble-transition-metal dichalcogenides - Miro, Pere; Ghorbani-Asl, Mahdi; Heine, Thomas (Angewandte Chemie International Edition, 2014)
The structure and electronic structure of layered noble-transition-metal dichalcogenides MX2 (M=Pt and Pd, and chalcogenides X=S, Se, and Te) have been investigated by periodic density functional theory (DFT) calculations. The MS2 monolayers are indirect band-gap semiconductors whereas the MSe2 and MTe2 analogues show significantly smaller band gap and can even become semimetallic or metallic materials. Under mechanical strain these MX2 materials become quasi-direct band-gap semiconductors. The mechanical-deformation and electron-transport properties of these materials indicate their potential application in flexible nanoelectronics. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: 2D materials; chalcogenides; noble metals; palladium; platinum